Simulation Analysis and Experimental Study on the Working State of Sinking Headframe in the Large Underground Shaft - Yin Qixiang; Zhao Weiping; Xin Wen; Yang Hailin; Zhang Linglei (Advances in Civil Engineering)
Based on the newly developed sinking headframe for the deep and large shaft, the finite element model of the full-scale headframe was established by using SAP2000. Through the calculation, the theoretical stress of the headframe at sinking depths of 40 m, 143 m, 223 m, 518 m, 762 m, 1000 m, 1250 m, and 1503 m was obtained and then compared with the field measured stress. The results show that with the increase of shaft sinking depth, the theoretical stress of finite element simulation and the field measured stress of each member of the sheave wheel platform and the headframe increase linearly, and for the maximum member stress in the upper, middle, and lower layers of the headframe, the numerical simulation value is greater than the field measured value and less than the designed steel strength. In other words, under normal working conditions, headframe members are in the elastic stress stage and meet the design requirements, and instability failure of headframe members will not occur. The end-restraint mode of the supporting bars has a great influence on the force of the top member. The reasonable selection of the restraint mode in the simulation is the key to the accuracy of the calculation results. The simulation results well reflect the actual stress of the headframe and provide a reliable guarantee for the follow-up work of the project.